ENDOVASCULAR TREATMENT FOR ACUTE DISORDERS OF MESENTERIC CIRCULATION - S. A. Prozorov; A. V. Grishin (Неотложная медицинская помощь)
An acute disorder of mesenteric circulation is a serious disease with high mortality. It occurs much more often due to the arterial flow impairment, and less often due to the venous blood flow disturbance. Etiology: thrombosis, embolism, compression of the lumen under dissection. To restore the mesenteric blood flow endovascular techniques are performed: mechanical recanalization, balloon angioplasty, stent installation, thrombolysis, tromboaspiration and their various combinations. If recanalization of the superior mesenteric artery is unable to be performed, hybrid operations are carried out anterogradely: retrograde stent installation during laparotomy. The review shows that endovascular methods is a promising direction of treatment for acute mesenteric ischemia.